Raw and extruded pea (Pisum sativum) and lupin (Lupinus albusvar. Multitalia) seeds as protein sources in weaned piglets’ diets: effect on growth rate and blood parameters - Gianfranco Piva; Francesco Masoero; Giorgio Fusconi; Maurizio Moschini; Mauro Morlacchini; Aldo Prandini (Italian Journal of Animal Science, 2010)
The 42 days trial was carried out using 140 piglets weaned at 28 days of age. The piglets were allocated according to  weight and sex to the 5 dietary treatments with 7 replicates for each treatments (4 pens x 4 castrated males and 3 pens  x 4 females). The piglets were fed according to the following experimental design: 1) control diet (CTR) with soybean  meal (SBM) 44% c.p. as protein source; 2) CRT diets with 200 g/kg of raw pea (Pisum sativum) (RP); 3) CTR diet with  200 g/kg extruded pea (EP); 4) CRT diet with 170 g/kg raw lupin (Lupinus albusvar. Multitalia) (RL); 5) CTR diet with  170 g/kg of extruded lupin (EL). During the trial, animals were weighed at 0 - 21 and 42 days from the start of the trial.  Feed intake was monitored and feed conversion ratio was calculated for the periods 0-21 d and 22-42 d. At the end of  the trial, blood samples were taken for 14 animals for each dietary treatment (2 animals per replicate) and analysed for  total protein, urea and liver activity (ALT, AST and ALP parameters). Average daily weight gain and feed intake did not  differ according to dietary treatments whereas during the total experimental period (0-42 d), feed conversion ratio was  higher for EP vsCTR diet (2.35 vs2.09, respectively; P <0.05). The growth rate for diets with extruded protein sources  compared with diets containing the raw ingredients did not differ. Feed conversion ratio for the RP was numerically high-  er than for the EP (2.35 vs2.16 and 2.76 vs2.32, respectively during 22-42 d and 0-42 d periods). Blood parameters  did not show significant difference among dietary treatments except for higher total protein for CTR diet vsRL diet, EL  and RP (67.3 vs62.2, 62.8 and 63.6 g/l, respectively; P<0.05) and urea that resulted the highest with CTR diet vsRL  and RL (4.7 vs3.7 and 3.8 mmol/l respectively; P<0.05).